2017
DOI: 10.1177/2047487317745177
|View full text |Cite
|
Sign up to set email alerts
|

Fitness attenuates the prevalence of increased coronary artery calcium in individuals with metabolic syndrome

Abstract: Fitness attenuates the prevalence of increased coronary artery calcium in individuals with metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…However, the findings from Bernaards et al [23] were not consistent with ours, potentially due to differences in assessments of fitness and methodology. Cardiorespiratory fitness has previously been found to be a stronger predictor for ill health compared with objectively assessed physical activity [46,47], which our results support.…”
Section: Discussionsupporting
confidence: 85%
“…However, the findings from Bernaards et al [23] were not consistent with ours, potentially due to differences in assessments of fitness and methodology. Cardiorespiratory fitness has previously been found to be a stronger predictor for ill health compared with objectively assessed physical activity [46,47], which our results support.…”
Section: Discussionsupporting
confidence: 85%
“…28 Coronary artery calcium, an independent predictor of coronary artery disease, was cross-sectionally studied among 678 middle-aged Swedes (52% women). 13 Among participants with moderate-high fitness (estimated by cycle ergometer test) the odds of having a high coronary artery calcium score was halved, compared to those with low fitness. Furthermore, MetS individuals had 47% higher odds for high coronary artery calcium score compared with those without MetS -however, moderate-high fitness seemed to partially attenuate this risk.…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, data from a few large population-based samples indicate that active participants with clustered CVD risk factors have similar risks of CVD and all-cause mortality to active participants without risk factors. [10][11][12][13] In individuals with impaired glucose tolerance, a combined intervention of increased PA and improved eating habits reduced the risk of type 2 diabetes, CVD and total mortality after 30 years. 14 However, the aforementioned studies are mainly targeting exercise i.e.…”
Section: Introductionmentioning
confidence: 99%
“…32 A recent study showed that physical activity is associated with a reduced risk of having significant coronary artery calcium in individuals with metabolic syndrome. 33 We found that the prevalence of active transport to work in England was low, but contest, therefore, that the potential to increase its uptake is great. 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 with MI was removed by local level estimates of smoking, diabetes and physical activity.…”
Section: Myocardial Infarctionmentioning
confidence: 78%
“…An increased prevalence of walking to work was associated with a reduced incidence of MI in men aged [25][26][27][28][29][30][31][32][33][34] In this national ecological study of over 40 million employed inhabitants of England aged 25-74 years of whom about 5 million were active transporters, the prevalence of walking to work was higher for women than men, and the prevalence of cycling to work was higher for men than women. In areas with increased levels of women walking and men cycling to work in 2011, the incidence of MI was reduced by 1.7% for women and men in 2012.…”
Section: Myocardial Infarctionmentioning
confidence: 99%